The Relationship Between Duration of Labor and Talking Hold in Post-Partum Mothers in The Working Area of The Akelamo Inpatient Community Health Center - Novlany Ayuba; Sulistiyah Sulistiyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Constipation is a common functional gastrointestinal problem in infants aged 6–12 months, causing discomfort, hard stools, and reduced quality of life. Non-pharmacologic interventions, such as abdominal massage, have shown promise in improving bowel function, but evidence regarding the effectiveness of the I Love You massage technique in community settings remains limited. Objective: This study aimed examine the effectiveness of I Love You massage in reducing constipation among infants aged 6–12 months attending South Bulango Health Center. Methods: A quasi-experimental design with a pretest-posttest control group was employed. Thirty infants with functional constipation were purposively selected and divided into an intervention group (n=15) receiving daily I Love You massage for 10 minutes over seven days, and control group (n=15) receiving standard care, including dietary guidance and hydration. Data were analyzed using SPSS version 25 with paired t-tests for within-group comparisons and independent t-tests for between-group differences. Results: The intervention group exhibited a significant increase in bowel movement frequency (2.1 ± 0.7 to 5.6 ± 0.9 per week) and improvement in stool consistency (1.2 ± 0.4 to 2.8 ± 0.5), along with a notable reduction in abdominal discomfort (6.5 ± 1.2 to 2.1 ± 0.8). In contrast, the control group showed minimal improvements. Statistical analysis confirmed significant differences between groups (p < 0.05). Conclusion: I Love You massage is an effective, safe, and low-cost intervention reduce constipation in infants aged 6–12 months. Its implementation in primary healthcare settings may enhance gastrointestinal function, relieve discomfort, and promote caregiver-infant interaction.